Original Article: Insensitivity of Platelet Aggregation to Inhibition by Prostaglandin I(2) (PGI(2)) and Prostaglandin E(1) (PGE(1)), and Reduced Platelet c-AMP Accumulation in Response to PGE(1) in Insulin-dependent Diabetic Patients - Zahavi, M; Kakkar, V V; Zahavi, J (Platelets (Edinburgh), 1995)
In insulin-dependent diabetics (IDDM) and peripheral occlusive arterial disease (POAD), inhibition of platelet aggregation (PA) by PGI(2) and PGE(1) was reduced (p <0.02) compared with non-diabetics and POAD as well as with healthy subjects at a similar extent of PA (in the 3 groups). c-AMP content in resting platelets of IDDM and chronic renal failure was decreased (mean ± SD in pmo1/2.5 × 10(8) platelets): 5.3 ± 1.1 compared with the content in healthy subjects: 8.0 ± 1.12 and P< 0.012. Moreover, c-AMP content in PGE(1)-stimulated platelets was also reduced in these patients. Our results indicate that diabetic patients are characteristically less sensitive to inhibition by the 2 prostanoids, presumably through attenuated activity of the c-AMP generating system.